2017
DOI: 10.1038/icb.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in systemic lupus erythematosus: far beyond Th1/Th2 dualism lupus: cytokine profiles

Abstract: The aims of this study were to delineate cytokine profiles of systemic lupus erythematosus (SLE), construct prediction models for diagnosis and disease activity using those profiles, and to examine the associations between TNFB Ncol polymorphism, body mass index (BMI) and vitamin D levels with cytokine levels. Two hundred SLE patients and 196 healthy controls participated in this case-control study. Plasma cytokines levels of tumor necrosis factor (TNF)-α, interferon (IFN)-γ, interleukin (IL)-1β, IL- 4, IL-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 48 publications
4
48
0
3
Order By: Relevance
“…IFN-γ is a pro-inflammatory cytokine that is associated with worse disease state in multiple malignancies and autoimmune disorders [2931]. IL-10 is classically known as an anti-inflammatory cytokine, but recent work has shown it has pro-inflammatory properties [3234]. Flt-3L levels can be elevated in hematological malignancies and autoimmune diseases [3538].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ is a pro-inflammatory cytokine that is associated with worse disease state in multiple malignancies and autoimmune disorders [2931]. IL-10 is classically known as an anti-inflammatory cytokine, but recent work has shown it has pro-inflammatory properties [3234]. Flt-3L levels can be elevated in hematological malignancies and autoimmune diseases [3538].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D treatment increased IL-10 production in T cells, reprogramming them to a less inflammatory T-helper 2 cell type [12]. However, more recent data have suggested that IL-10 may have pro-inflammatory properties [3234]. It is also a known transcriptional target of STAT3 and can positively regulate STAT3 signaling [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that IL-12 was upregulated in serum of patients at the active stage of SLE, while others reported defective IL-12 production in lupus patients [36,42]. As for IFN-γ, divergences were not so obvious and past literatures tend to suggest that serum levels of IFN-γ were higher in lupus patients than in controls [10][11][12][13][14][15]. In addition, IFN-γ was also associated with symptomatology of SLE, in which a subtle correlation was found between SLEDAI scores and serum IL-4/IFN-γ ratios and evident correlation of IFN-γ with SLAM scores was also documented [16,17].…”
Section: Discussionmentioning
confidence: 97%
“…The damages of diverse organ and tissue are caused by different immune responses in SLE. The hormonal factors closely related to capillary damage in glomeruli, lungs, dermal tissues while damage for interstitium of kidneys, lacrimal, and salivary glands were caused by cell-mediated immunity [66,67]. Therefore, investigators thought single cytokinetargeted therapy might not be adequate because of complex cytokine network but a certain cytokine targeted therapy had potent effects with cascade reaction of immune response.…”
Section: Il-12 and Ifn-γ Targeted Therapy For Slementioning
confidence: 99%
See 1 more Smart Citation